Automated analysis of intestinal polyps images - I. V. Yarema; A. N. Gerasimov; N. F. Lebedeva; O. M. Kharkova; A. A. Atayan (Сеченовский вестник)
Using image analysis software calculates the distribution of points of polyp bowel picture brightness and color, as well as the rate of brightness and color gradients. Next, using statistical analysis founds connection with clinical indicators of image characteristics. It was found that the calculated characteristics allow to determine accurately the diagnosis.